2015
DOI: 10.1002/cssc.201403230
|View full text |Cite
|
Sign up to set email alerts
|

Polar Group and Defect Engineering in a Metal–Organic Framework: Synergistic Promotion of Carbon Dioxide Sorption and Conversion

Abstract: A sulfone-functionalized metal-organic framework (MOF), USTC-253, has been synthesized that exhibits a much higher CO2 uptake capacity (168-182 %) than the corresponding unfurnished MOFs. The introduction of trifluoroacetic acid (TFA) during the synthesis of USTC-253 affords defect-containing USTC-253-TFA with exposed metal centers, which has an increased CO2 uptake (167 %) compared to pristine USTC-253. USTC-253-TFA exhibits a very high ideal adsorption solution theory selectivity (S=75) to CO2 over N2 at 298… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(112 citation statements)
references
References 96 publications
9
103
0
Order By: Relevance
“…The nickel wire (length 3cm, diameter about 0.4 mm) was put into ab ottle containing the mixture of H 2 btzip (0.015 g, 0.05 mmol), acetonitrile (4 mL), DMF (4 mL), and two drops of HCl (1.0 mol L À1 ). The capped bottle was heated at 115 8Cf or 72 h, and then cooled to room temperature, gaining blue sheet-like crystals in 52.0 % yield (based on H 2 btzip);e lemental analysis calcd (%) for C 30…”
Section: Synthesis Of [Ni(btzip)(h 2 Btzip)]·2dmf·2 H 2 O( 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…The nickel wire (length 3cm, diameter about 0.4 mm) was put into ab ottle containing the mixture of H 2 btzip (0.015 g, 0.05 mmol), acetonitrile (4 mL), DMF (4 mL), and two drops of HCl (1.0 mol L À1 ). The capped bottle was heated at 115 8Cf or 72 h, and then cooled to room temperature, gaining blue sheet-like crystals in 52.0 % yield (based on H 2 btzip);e lemental analysis calcd (%) for C 30…”
Section: Synthesis Of [Ni(btzip)(h 2 Btzip)]·2dmf·2 H 2 O( 1)mentioning
confidence: 99%
“…[19,20] Wherein, the existence of accessible open metal sites (OMSs)a nd/ora cidic groupsi nt he pores are crucial for the catalytica ctivity of MOFs, which serve not only as CO 2 -binding sites but also as Lewis and/or Brønsted acidic catalytic sites. [21][22][23][24][25][26][27][28][29][30][31][32] Notably,i nt hese MOF catalysts, the major catalytic sites are Lewis acidic OMSs, which are generated by the removal of coordinated solvents at high temperatures, however,t he harsh activationc onditions usually lead to the framework incompleteness to ad egree. In contrast,t he deliberate embedding of Brønsteda cidic sites in MOFs is an alternative andw orth anticipating approacht oa chieve the capture of CO 2 and its catalytic conversion with epoxides,w hereas related reports are rarely documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the promising approaches to mitigate the CO 2 emission is the chemical fixation of CO 2 into value‐added products. Since CO 2 can be considered an inexpensive, nontoxic, and nearly inexhaustible C1 feedstock, a large amount of studies have been undertaken to convert CO 2 into synthetically valuable products that are currently derived from petroleum sources, including the reaction with alcohols to produce carbonates, the reaction with epoxides to form cyclic carbonates, C−C bond formation by reaction with unsaturated hydrocarbons, and direct hydroformylation instead of using CO gas to produce alcohols from alkenes . Alternatively, hydrogenation of CO 2 to produce formic acid (FA; HCOOH) has currently received considerable attention, since FA has been regarded as a promising H 2 storage compound with alluring intrinsic properties (high hydrogen content (4.4 wt %), liquid at room temperature, easy‐handling and safe storage) .…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, many heterogeneous catalysts have been developed in the last few decades, such as metal oxides, polymeric/supported ionic liquids, modified graphitic carbon nitride, MOFs, and functional polymers . Notably, it was reported that MOFs, such as {Cu 4 [(C 57 H 32 N 12 )(COO) 8 ]} n (room temperature (RT), 1 atm, 48 h), MMCF‐2 (RT, 1 atm, 48 h), Hf‐NU‐1000 (RT, 1 atm, 26 h), USTC‐253‐TFA (RT, 1 atm, 72 h), MMPF‐18 (RT, 1 atm, 48 h), and a Zn‐based anionic MOF (RT, 1 atm, 48 h), coupled with a nucleophilic cocatalyst (quaternary ammonium halide) could realize the chemical fixation of CO 2 at ambient CO 2 pressure or even at ambient temperature . Although the long reaction time made the synthesis process inefficient, the cost of the synthesis of the catalyst was unsatisfactory for practical application.…”
Section: Introductionmentioning
confidence: 99%